Is MYR/USD a random walk? New evidence from the BDS test - Lim, Kian Ping; Mohamed, Azali; Lee, Hock Ann (Universiti Putra Malaysia Press, 2003)
This study empirically investigates the daily MYR/USD exchange rate return series in the light of the random walk hypothesis. Recent breakthroughs pertaining to non-linear dynamics and chaos, coupled with the rapid acceleration in computer power, have made it possible to more robustly test for the random walk in financial and economic data. This study uses a new non-linear statistical test, namely the Brock-Dechert-Scheinkman (BDS) test to examine whether the MYR/USD exchange rate return series are random walk with the property of being independent and identically distributed. The results overwhelmingly reject the hypothesis that the MYR/USD data examined in this study are random, independent and identically distributed since some cycles or patterns show up more frequently than would be expected in a true random series. These results may have implications for the weak form market efficiency, if the underlying structure can be profitably exploitable, which remains an avenue for further research.